General review of conditionsof employment of public servants - International Labour Organisation (Geneva : International Labour Office, 1970)
The present report covers all public officials and employees, both established and non-established, temporary and permanent, employed in: (a) central government departments and national autonomous public institutions of a non-industrial and non-commercial nature and; (b) local public authorities and local autonomous public institutions of a non-industrial and non-commercial nature.
Joint Committee on the Public Service.
Includes bibliographical references.
ne 29/06/2018
Loans
Keywords: Public service (Civil service).